Correlation of quantitative measures of estrogen receptor α and β expression in non-small cell lung cancer tissue with clinical characteristics of the disease - T. A. Bogush; S. A. Samsonik; A. A. Basharina; E. A. Bogush; O. M. Ryabinina; A. N. Grishanina; V. Yu. Kirsanov; A. V. Karpukhin; V. S. Kosorukov (Антибиотики и Химиотерапия)
The expression level of estrogen receptors (ERα and ERβ) in surgical tumor biopsy specimens from 167 patients with non-small cell lung cancer (NSCLC) was quantiﬁed by ﬂow cytometry-based immunoﬂuorescence analysis. ERα and ERβ expression was revealed in all the tumor samples investigated. The level of ERα expression in the tumors varied from 10 to 58% and ERβ — 12% to 80%, indicating signiﬁcant heterogeneity of estrogen receptor expression in tumors of diﬀerent patients. The mean ERβ expression level was approximately 2-times higher compared to ERα (42.1±15.3% vs 21.4±11.3%; p<0.001). It allows to consider ER>β as a major estrogen target in NSCLC tissue. The level of ERα and ERβ expression in NSCLC tissue is independent of gender, smoking status, and the histological type of the tumor. Increased ERβ expression was detected only in male patients with lung adenocarcinoma in comparison with squamous cell carcinoma (p=0.02). The assessment of the correlation between ERα and ERβ in both the whole cohort of patients and subgroups with clinically relevant disease parameters revealed that the level of one marker does not predict the other one’s expression. The coeﬃcient of determination, which characterizes how diﬀerences in one variable can be explained by the diﬀerence in a second variable, was less than 25% in any comparison group. The authors consider that the high level of ERβ expression and ERα coexpression in NSCLC tissue substantiates the clinical perceptiveness of a new treatment option for the disease, namely, adjuvant hormone (antiestrogen) therapy.